Melatonin supplementation counteracts fiber loss in knee ligaments of diabetes-induced rats - Adamska, Olga; Wnuk, Artur; Kamińska, Agnieszka; Poniatowska, Małgorzata; Maciąg, Bartosz; Kamiński, Maciej; Stolarczyk, Artur; Matin, Maima; Atanasov, Atanas G.; Łapiński, Marcin; Jóźwik, Artur (Frontiers in Pharmacology, 2024)
Diabetes mellitus (DM) is a prevalent metabolic disease. The clinical impact of the effect of sustained hyperglycemia on ligament healing has not been well characterized. Diabetes is a known cause of macro-, microvascular and diabetic ulcers healing difficulties among tissues. Therefore, we aimed to investigate the healing potential occurring in injured and healthy ligaments among diabetic and healthy individuals using a rat model. We hypothesize that DM may contribute to the knee medial collateral ligament (MCL) alteration, thus its morphology, biochemical fitness and functionality. The study cohort consisted of 40 rats. The animals were randomized into four equal groups. The I and II groups (20 rats) received saline subcutaneously and continued to function as controls. The III and IV groups (20 rats) were injected with a single dose of streptozotocin (STZ). at a dose of 60 mg/kg body weight., dissolved in freshly prepared buffer (0.1 mol/L citrate, pH 4.5). All animals underwent surgery to cut the left tibial collateral ligament in the hind limb and suture it and suture the access site to create inflammation to study the regenerative capacity of animals with normal carbohydrate metabolism and with pharmacologically induced diabetes. Each animal then underwent sham surgery to access and suture the right tibial collateral ligament in the hind limb without ligament intervention. After the animals had undergone surgeries, groups II and IV were given melatonin supplementation for 4 weeks. There was a significant positive correlation between high fasting plasma glucose values and body weight and degree of elastin degradation, fibrosis and calcifications. Compared with the control group, left MCL appearance was significantly more fibrotic, collagen arrangement was more disordered and presented with qualitative measures in the DM group. Diabetes intensifies the age-related changes across ligamentous components of the musculoskeletal system in rats. DM induction provoked excessive weight gain in the experimental group, which positively correlated with the decreased healing potential. Rats with DM presented with more fibrosis and calcifications of MCL and decreased healing potential. Treatment with melatonin in diabetic rats mitigated alterations and improved the antioxidant status of ligaments from the diabetic group.